Integrated characterization and risk management of marine sediments: The case study of the industrialized Bagnoli area (Naples, Italy). (September 2020) - Morroni, Lorenzo; d'Errico, Giuseppe; Sacchi, Marco; Molisso, Flavia; Armiento, Giovanna; Chiavarini, Salvatore; Rimauro, Juri; Guida, Marco; Siciliano, Antonietta; Ceparano, Mariateresa; Aliberti, Francesco; Tosti, Elisabetta; et al.
Abstract: The aim of the present work is to demonstrate the practical importance of a multidisciplinary approach and weighted criteria to synthesize and integrate different typologies of data (or lines of evidence, LOEs), including chemical levels in marine sediments, their bioavailability to specific indicator species, ecotoxicological effects measured through subcellular biomarkers and batteries of bioassays, and potential impacts of pollution on local benthic communities. The area of Bagnoli (Gulf of Naples, Southern Italy) was selected as a model case-study, as it is a coastal area chronically impacted by massive industrial contamination (trace metals and hydrocarbons), and dismissed decades ago without any subsequent remediation or habitat restoration. The results of each LOE were elaborated to provide specific hazard indices before their overall integration in a weight of evidence (WOE) evaluation. Levels of some trace metals and PAHs revealed a severe contamination in the entire study area. Bioavailability of hydrocarbons was evident particularly for high molecular weight PAHs, which also caused significant variations of cellular biomarkers, such as cytochrome P450 metabolization in fish, lysosomal membrane destabilization in mussels, genotoxic effects both in fish and molluscs. The results of a battery of bioassays indicated less marked responses compared to those obtained from chemical and biomarkers analyses, with acute toxicity still present in sediments close to the source of contamination. The analysis of benthic assemblages showed limited evidence of impact in the whole area, indicating a good functioning of local ecosystems at chronic contamination. Overall, the results of this study confirm the need of combining chemical and biological data, the quantitative characterization of various typologies of hazard and the importance of assessing an integrated environmental WOE risk, to orientate specific and scientifically-supported management options in industrialized areas. Highlights: Extremely high levels of some metals and PAHs occur in sediments. HMW-PAHs are bioavailable to local sentinel species. Biomarkers reveal subtle adverse effects of PAHs. Ecotoxicological bioassays indicate less marked acute effects. WOE provides an integrated assessment of environmental health status.